Fiscal Adjustment and Growth in Sub-Saharan Africa : Overview and Lessons from the Current Downturn - Fofack, Hippolyte (2012)
In light of the proliferation of exceptionally large fiscal stimuli to ward off the recession triggered by the 2008 global economic and financial crisis in most advanced economies, this paper revisits the fiscal adjustment and growth nexus in Sub-Saharan Africa. Using transfer functions, it quantifies expected losses in terms of aggregate output largely attributed to a systematic implementation of pro-cyclical expenditure switching and reducing policies to achieve low deficit targets throughout the decades of adjustments. The results consistently highlight a much higher predicted aggregate output under the hypothesized counter-cyclical fiscal expansion option. This consistent outcome suggests that the output gap would have been significantly smaller in the region if countries had drawn on stop-and-go policies of fiscal expansion to sustainably raise the stock of capital investments.